Personal Financial Management Behavior of Students in Bali - Putu Eva Julianawati; Putu Siti Firmani; Ni Putu Devi Ary Santhi; I Ketut Sudana (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the influence of financial literacy, financial knowledge, financial attitudes, and budget planning on the personal financial management behavior of college students in Bali. The research method used was a quantitative approach with descriptive and inferential analysis, as well as multiple linear regression analysis techniques on data obtained from respondents. The results indicate that, both partially and simultaneously, financial literacy, financial knowledge, financial attitudes, and budget planning have a positive and significant influence on college students' personal financial management behavior, with budget planning being the most dominant variable. Furthermore, the coefficient of determination indicates that the research model can explain 13.4% of the variation in financial behavior, while the remainder is influenced by factors outside the model. These findings emphasize the importance of improving financial education and budget planning practices in shaping better college students' financial behavior.